Catalytic asymmetric deuterosilylation of exocyclic olefins with mannose-derived thiols and deuterium oxide. Issue 5 (23rd January 2023) - Ramanathan, Devenderan; Shi, Qinglong; Xu, Meichen; Chang, Rui; Peñín, Beatriz; Funes-Ardoiz, Ignacio; Ye, Juntao
Abstract : Metal-free, photoinduced asymmetric deuterosilylation of exocyclic olefins has been achieved using a mannose-derived thiol catalyst. Abstract : Here we report a photochemical approach for asymmetric deuterosilylation of exocyclic olefins by utilizing mannose-derived thiols as the chiral catalyst and inexpensive deuterium oxide as the deuterium source. DFT computational studies reveal that multiple non-covalent interactions between the thiol catalyst and the radical adduct are responsible for controlling the enantioselectivity of the reaction.